2007
DOI: 10.1016/j.neuroimage.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

An ERP study of regular and irregular English past tense inflection

Abstract: Compositionality is a critical and universal characteristic of human language. It is found at numerous levels, including the combination of morphemes into words and of words into phrases and sentences. These compositional patterns can generally be characterized by rules. For example, the past tense of most English verbs ("regulars") is formed by adding an -ed suffix. However, many complex linguistic forms have rather idiosyncratic mappings. For example, "irregular" English verbs have past tense forms that cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
52
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 82 publications
17
52
2
2
Order By: Relevance
“…e.g., Avrutin, 1999Avrutin, , 2004Chierchia, 1998), we wanted to see whether it would be possible to narrow down the source of the processing costs. In this respect, ERPs are useful measures to distinguish between a left anterior negativity (LAN) for morphosyntactic costs (e.g., Osterhout & Mobley, 1995;Newman, Ullman, Pancheva, Waligura, & Neville, 2007) and a more broadly distributed negativity (N400) for costs involving discourse-semantic memory (e.g., Burkhardt, 2006;Van Berkum, Brown, & Hagoort, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…e.g., Avrutin, 1999Avrutin, , 2004Chierchia, 1998), we wanted to see whether it would be possible to narrow down the source of the processing costs. In this respect, ERPs are useful measures to distinguish between a left anterior negativity (LAN) for morphosyntactic costs (e.g., Osterhout & Mobley, 1995;Newman, Ullman, Pancheva, Waligura, & Neville, 2007) and a more broadly distributed negativity (N400) for costs involving discourse-semantic memory (e.g., Burkhardt, 2006;Van Berkum, Brown, & Hagoort, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although fMRI (functional Magnetic Resonance Imaging) (Ullman et al 1997;Huang et al 2002;Beretta et al 2003), ERP (Event-related potential) (Newman et al 2007) and PET (Positron Emission Tomography) (Jaeger et al 1996;Indefrey et al 1997) studies have revealed that different cerebral regions are active during regular and irregular inflection processing and that irregular forms are processed relatively slower, a metaanalysis (Indefrey 2000) has shown that: What is more, the development o f irregular past tense verbs depends on their frequency (Shipley et al 1991). No such in-depth research has been conducted specifically for the Polish language so far.…”
Section: Lingua Ex M Achina?mentioning
confidence: 99%
“…For the English language, for instance, many studies (NEWMAN; ULLMAN, 2007;ULMMAN, 2001ULMMAN, , 2004ULMMAN, , 2005PRASADA;PINKER, 1993) have shown that the processing of high-frequency and low-frequency regular forms are not correlated with their frequencies, but that speakers of English process high-frequency irregular verbs faster than low-frequency irregular verbs. These findings suggest that speakers of English activate a computational mechanism to process regular forms (by concatenating a base to a suffix: walk + ed in language production or decomposing the items into their morphological constituents in language comprehension), but rely on memory to process irregular forms.…”
Section: Introductionmentioning
confidence: 99%